The Roles of the Tribunal, the Courts and the Legislature - Keith, Kenneth J (Victoria University of Wellington Law Review, 1995)
This article discusses the roles of the Tribunal, the courts, and the legislature in handling Treaty of Waitangi claims. The author first discusses the allocation of roles among those bodies by exploring the constitutional role of the Treaty, the legislation giving effect to the Treaty, the Treaty legislation being tested in the courts, and the criteria for allocation of public powers of decision. The article then raises broader issues about the Treaty and the constitution, suggesting that power should not always be thought of in a top-down approach. The author suggests some possible arrangements that could facilitate this approach including allowing for Māori self-determination, the power of veto for Māori, and limiting the exercise of public power. This article also contains a question and answer session with Sir Kenneth Keith.